Cling together, swing together: The contagious effects of COVID-19 on developing countries through global value chains - Stefan Pahl; Clara Brandi; Jakob Schwab; Frederik Stender (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
This paper aims at estimating the economic vulnerability of developing countries to disruptions in global value chains (GVCs) due to the COVID-19 pandemic. It uses data on trade in value-added for a sample of 12 developing countries in sub-Saharan Africa, Asia and Latin America to assess their dependence on demand and supply from the three main hubs China, Europe, and North America. Using first estimates on COVID-19-induced changes in production and sectoral final demand, we obtain an early projection of the GDP effect during the lockdowns that runs through trade in GVCs. Our estimates reveal that adverse demand-side effects reduce GDP by up to 5.4 per cent, and that collapsing foreign supply is responsible for a drop in GDP of a similar magnitude. Overall, we confirm conjecture that the countries most affected are those highly integrated into GVCs (Southeast Asian countries). We argue, however, that these countries also benefit from a well-diversified portfolio of foreign suppliers, leading to a cushioning of economic downswing from adverse supply-side spillovers, because COVID-19 stroke major hubs at different times during the first wave in early 2020. Moreover, despite expected hazardous home market effects, sub-Saharan Africa's GDP appears to be comparatively less affected though GVCs due to a lack of intensive supply- and demand-side dependencies.
Keywords: 330; COVID-19; global value chains; input-output analysis; international trade; supply- and demand-side dependency; shock spillover